Proinflammatory Cytokine Environments Can Drive Interleukin‐17 Overexpression by γ/δ T Cells in Systemic Juvenile Idiopathic Arthritis. Issue 7 (12th June 2017) - Kessel, Christoph; Lippitz, Katrin; Weinhage, Toni; Hinze, Claas; Wittkowski, Helmut; Holzinger, Dirk; Fall, Ndate; Grom, Alexei A.; Gruen, Niklas; Foell, Dirk
Abstract : Objective: Systemic‐onset juvenile idiopathic arthritis (JIA) is speculated to follow a biphasic course, with an initial systemic disease phase driven by innate immune mechanisms and interleukin‐1β (IL‐1β) as a key cytokine and a second chronic arthritic phase that may be dominated by adaptive immunity and cytokines such as IL‐17A. Although a recent mouse model points to a critical role of IL‐17–expressing γ/δ T cells in disease pathology, in humans, both the prevalence of IL‐17 and the role of IL‐17–producing cells are still unclear. Methods: Serum samples from systemic JIA patients and healthy pediatric controls were analyzed for the levels of IL‐17A and related cytokines. Whole blood samples were studied for cellular expression of IL‐17 and interferon‐γ (IFNγ). CD4+ and γ/δ T cells isolated from the patients and controls were assayed for cytokine secretion in different culture systems. Results: IL‐17A was prevalent in sera from patients with active systemic JIA, while both ex vivo and in vitro experiments revealed that γ/δ T cells overexpressed this cytokine. This was not seen with CD4+ T cells, which expressed strikingly low levels of IFNγ. Therapeutic IL‐1 blockade was associated with partial normalization of both cytokine expression phenotypes. Furthermore, culturing healthy donor γ/δ T cells in serum from systemic JIA patients or in medium spiked with IL‐1β, IL‐18, and S100A12 induced IL‐17 overexpression at levels similar to those observed in the patients' cells. Conclusion: A systemic JIA cytokine environment may prime γ/δ T cells in particular for IL‐17A overexpression. Thus, our observations in systemic JIA patients strongly support a pathophysiologic role of these cells, as proposed by the recent murine model.